Haemorrhagic Corpus Luteum Mimic Appendicitis (TAJ: Journal of Teachers Association, 2009)
Haemoperitoneum secondary to ruptured corpus luteum is a rare complication for women of reproductive life. The differential diagnosis of hemoperitoneum includes various of acute abdomen that usually associated with acute lower abdominal pain and swelling lower abdomen. The differential diagnosis includes ruptured ectopic pregnancy, ruptured chocolate cyst, twisted ovarian tumor, pelvic inflammatory disease and pelvic peritonitis. Ruptured hemorrhagic corpus luteum is an uncommon cause of acute abdomen. Its occurrence is unknown but is likely quite frequent and without symptoms. Most cases are self-limiting; enquire only observation with abdominal pain relieved with analgesics. Some need laparoscopy or laparotomy to achieve homeostasis if the patient is haemodynamically unstable.TAJ 2009; 22(1): 276-278